PENERAPAN E-LEARNING DENGAN PENDEKATAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) BERBASIS WEBSITE PADA SEKOLAH MENENGAH PERTAMA - Wiyanto Wiyanto; Muhammad Najmuddin Dwi Miharja (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Junior High School (SMP) is the first level school in Indonesia. The current learning system still uses a lot of conventional learning systems, namely the learning process is still bound by time and face-to-face in class between teachers and students. So that students become passive because they are dominant in listening to the lecture method. In this case an effective learning system with an online-based learning system is needed, namely E-learning with a Website-based Customer Relationship Management (CRM) approach at SMP using PHP programming tools and testing using ISO 9126. This is to assist and provide solutions in the learning process at the junior high school level in order to make it easier for students to study without a period of time determined by the school and to be able to study independently. The application of E-learning with a website-based CRM approach by testing using the ISO 9126 model with very good results of 87.56%, this is expected to increase students' interest and creativity in the learning process using computers, laptops and even smartphones